Party Politics and political violence in Bangladesh: issues, manifestation and consequences - Moniruzzaman, Md. (SAGE, 2009)
This article analyses the causes, manifestation and consequences of political violence in Bangladesh. The analysis is based on two arguments: fi rst, that there is a cyclical relationship between inter-party confl ict, political violence, and inter-party enmity; and secondly, interparty confl ict and violence at the horizontal level leads to political non-cooperation and stalemate at the vertical level between the ruling party and the opposition. Political violence emerges from a deep rooted political culture of intolerance, antagonism, revenge and arrogance. Apparent immediate causes of political violence are expressions of underlying differences and rifts along the lines of ideological, political, religious and institutional dimensions. Political violence results in distrust, institutionalisation of violence as a legitimate means of political expression and socialisation of violence-politics for the new generation of party loyalists.